2015
DOI: 10.1080/21645515.2015.1085142
|View full text |Cite
|
Sign up to set email alerts
|

Local infiltration of rabies immunoglobulins without systemic intramuscular administration: An alternative cost effective approach for passive immunization against rabies

Abstract: Presently the dose of rabies immunoglobulin (RIG) which is an integral part of rabies post exposure prophylaxis (PEP) is calculated based on body weight though the recommendation is to infiltrate the wound(s). This practice demands large quantities of RIG which may be unaffordable to many patients. In this background, we conducted this study to know if the quantity and cost of RIG can be reduced by restricting passive immunization to local infiltration alone and avoiding systemic intramuscular administration b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 9 publications
0
57
0
1
Order By: Relevance
“…Due to limited RIG availability, patients (N = 700, median age: 30 years, median weight: 53 kg, sex ratio: 63:37 male:female) were administered RIG under a dose-sparing approach of infiltration of the wound only. All survived on follow-up [8,9]. We used bootstrap sampling of these data, where patient weight was measured, to capture variability in RIG use under two scenarios: (1) infiltration at the wound (s) with the remainder administered intramuscularly distant from the wound; and (2) infiltration of the wound(s) only.…”
Section: Rig Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to limited RIG availability, patients (N = 700, median age: 30 years, median weight: 53 kg, sex ratio: 63:37 male:female) were administered RIG under a dose-sparing approach of infiltration of the wound only. All survived on follow-up [8,9]. We used bootstrap sampling of these data, where patient weight was measured, to capture variability in RIG use under two scenarios: (1) infiltration at the wound (s) with the remainder administered intramuscularly distant from the wound; and (2) infiltration of the wound(s) only.…”
Section: Rig Deliverymentioning
confidence: 99%
“…The previous WHO recommendation calculates dosage according to patient body weight, with as much RIG as is anatomically possible being administered into and around the wound(s) and the remaining product being injected intramuscularly distant from the wound [4]. New evidence led to revised protocols for administering RIG at the wound only [8,9]. RIG vials can be shared between patients using single-use injection devices, but opened vials should also be discarded at the end of each day.…”
Section: Introductionmentioning
confidence: 99%
“…1 One major barrier to Post Exposure Prophylaxis (PEP) continues to be the high cost of rabies immunoglobulins (RIG) which can be bridged by injecting RIG into the wounds only, and omitting intramuscular administration of the remaining part that was not used for wound injection. 2 An increasing number of dog bite victims were being presented to public hospitals in Himachal Pradesh, India in 2014 amidst virtual non availability of RIG. 2 Only a small quantity of eRIG was available from the government owned Central Research Institute (CRI) Kasauli.…”
mentioning
confidence: 99%
“…2 An increasing number of dog bite victims were being presented to public hospitals in Himachal Pradesh, India in 2014 amidst virtual non availability of RIG. 2 Only a small quantity of eRIG was available from the government owned Central Research Institute (CRI) Kasauli. We were 'forced' to do this study given limited availability of eRIG.…”
mentioning
confidence: 99%
“…A recent study by Bharti and Madhusudana et al has shown that local infiltration of rabies immunoglobulins (RIGs) in and around wounds [8] is effective in preventing rabies even in lab confirmed rabid dog bite human patients and prompted us to do this study in animals to save their lives.…”
Section: Introductionmentioning
confidence: 99%